PENGEMBANGAN BAHAN AJAR MENGANALISIS UNSUR PEMBANGUN PUISI BERBASIS PENDIDIKAN KARAKTER DI SISWA KELAS X SMA NEGERI 4 KOTA LUBUKLINGGAU - Masyitoh, Siti; Nugroho, Agung; Juwati, Juwati (LPPM Universitas PGRI Silampari Lubuklinggau, 2025)
This study aims to produce teaching materials in the form of LKPD analyzing the elements of poetry building based on character education. This study uses the Research and Development (R&D) method with the ADDIE model used to develop teaching materials in the form of LKPD analyzing the elements of poetry building based on character education. The population and sample or research subjects were students of SMA Negeri 4 Lubuklinggau City, precisely class X.9. Data collection techniques in this study were tests, interviews and questionnaires. While the data analysis technique for validity used Aiken's V, practicality used a Likert scale, and effectiveness used the N-gain score. The results of the study prove that LKPD analyzing the elements of poetry building based on character education is valid, practical, and effective. Validation obtained a